Benefits of increasing skills in the care workforce in recognising end of life in dementia patients. Issue 2 (1st June 2012) - Bloomer, C.; Thorn, M.
Abstract : Delivery of End of life care for dementia sufferers in any setting can be very varied with an undue emphasis on a medical and pharmacological model of care. Planning for the end of life for dementia suffers should be based on life story work, engaging the patient and families enhancing the choices for dementia sufferers at the end of life. Commissioned by the NHS to create, pilot and establish a training programme enhancing the skills of the care workforce. This project was designed to improve staff confidence in their ability to plan and assess symptoms for dementia sufferers at the end of life. Training needs analysis demonstrated that there was a requirement for providing participants with a basic understanding of the functions of, and how dementia affects, the brain in order for staff to better understand symptoms and behaviours at the end of life. The training, delivered to all levels of care home staff, comprises of a half day workshop with presentations from an Expert by Experience, from the local hospice on the use of medication at the end of life plus physiology and life story work. The DVD produced as part of the project provided a positive rather than a negative slant on dementia care and there was a self-assessment element both prior to and after the training including a post training evaluation form. The evaluations showed enhanced knowledge and confidence in skills. Attendees felt that the DVD and course workbooks became a good reference source for on-going practice.